2022
DOI: 10.1073/pnas.2210595119
|View full text |Cite
|
Sign up to set email alerts
|

EBF1 is continuously required for stabilizing local chromatin accessibility in pro-B cells

Abstract: The establishment of de novo chromatin accessibility in lymphoid progenitors requires the “pioneering” function of transcription factor (TF) early B cell factor 1 (EBF1), which binds to naïve chromatin and induces accessibility by recruiting the BRG1 chromatin remodeler subunit. However, it remains unclear whether the function of EBF1 is continuously required for stabilizing local chromatin accessibility. To this end, we replaced EBF1 by EBF1-FKBP F36V in pro-B cells, allowing the rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The CTD of EBF1 is also involved in the recruitment of BRG1 and in chromatin opening at CTD-dependent sites ( Wang et al 2020 ). In addition to stabilizing initial EBF1 binding, BRG1 association is required for maintaining an open chromatin state at CTD-dependent sites of EBF1 occupancy ( Zolotarev et al 2022 ). ChIP-qPCR analysis indicated that BRG1 binding at CTD-independent sites is similar in wt-, ΔC-, and Y > A-expressing cells, whereas BRG1 binding at CTD-dependent sites was reduced in ΔC- and Y > A-expressing cells relative to wt-expressing cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CTD of EBF1 is also involved in the recruitment of BRG1 and in chromatin opening at CTD-dependent sites ( Wang et al 2020 ). In addition to stabilizing initial EBF1 binding, BRG1 association is required for maintaining an open chromatin state at CTD-dependent sites of EBF1 occupancy ( Zolotarev et al 2022 ). ChIP-qPCR analysis indicated that BRG1 binding at CTD-independent sites is similar in wt-, ΔC-, and Y > A-expressing cells, whereas BRG1 binding at CTD-dependent sites was reduced in ΔC- and Y > A-expressing cells relative to wt-expressing cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GFP + CD19 + cells were sorted for ATAC-seq and RNA preparation. ATAC-seq was performed using self-made loaded Tagmentase according to a previously published protocol ( Zolotarev et al 2022 ), with some changes outlined in the Supplemental Material . RNA was purified using the Qiagen RNeasy kit according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…EBNA2 relieves this repression, thereby activating RBPJ target genes, including MYC. In parallel, through its N-terminal domain, EBNA2 recruits Early B Cell Factor 1 (EBF1/OLF-1/COE1) ( 23 ), a pioneer transcription factor that specifies and maintains B cell lineage ( 24 ). EBF1 binding by EBNA2 is necessary for full oncogenic hyperactivation of MYC, to promote metabolic processes linked to cell cycle progression, thereby maintaining B cells in their EBV-driven, proliferating, immortalized state ( 20 ).…”
Section: Introductionmentioning
confidence: 99%